B cell development in mice that lack one or both immunoglobulin kappa light chain genes. - Chen, J (1993)
We have generated mice that lack the ability to produce immunoglobulin (Ig) kappa light chains by targeted deletion of J kappa and C kappa gene segments and the intervening sequences in mouse embryonic stem cells. In wild type mice, approximately 95% of B cells express kappa light chains and only approximately 5% express lambda light chains. Mice heterozygous for the J kappa C kappa deletion have approximately 2-fold more lambda+ B cells than wild-type littermates. Compared with normal mice, homozygous mutants for the J kappa C kappa deletion have about half the number of B cells in both the newly generated and the peripheral B cell compartments, and all of these B cells express lambda light chains in their Ig. Therefore, homozygous mutant mice appear to produce lambda-expressing cells at nearly 10 times the rate observed in normal mice. These findings demonstrate that kappa gene assembly and/or expression is not a prerequisite for lambda gene assembly and expression. Furthermore, there is no detectable rearrangement of 3' kappa RS sequences in lambda+ B cells of the homozygous mutant mice, thus rearrangements of these sequences, per se, is not required for lambda light chain gene assembly. We discuss these findings in the context of their implications for the control of Ig light chain gene rearrangement and potential applications of the mutant animals.